A Bánság etnikai-kulturális közösségei a XX. század elején - Kókai, Sándor (Közép-Európai Közlemények, 2010)
The Bánság was a unique cultural area in the historical Hungary, since then it mostly disappeared as the ethnical and linguistic rate changed. At the same time it is still a special cultural geographical region in the Carpathian-Basin. The Bánság’s cultural diversity is originated thanks to thesenations: Romanians, Germans, Hungarians, Serbs, Croatians, Jewish, Bulgarians, Slovaks, Czechs, Gypsies, Turkish. The religious variety is also characteristic because of the large number of religions (Orthodox, Catholicism, Protestant, Calvinist, Jewish and Muslim denomination). The Bánság was the model of peaceful coexistence between 1718 and 1918. Nowadays the maintenance of intercultural heritage is in danger. The region lost the multilingual character, which would mean connection with West-Europe.